PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA USAHA CUCI STEAM RAHMAT MULAK ULU KABUPATEN LAHAT - Tri Rusilawati (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
Influence of Service Quality Customer Satisfaction At Mercy Steam Cleaner Mulak Ulu Lahat. This study basically discusses the Influence of Service Quality Customer Satisfaction In Effort Pressure Cleaning Grace Mulak Ulu Lahat, the objectives of this research was to determine the effect of service quality to customer satisfaction in the washing business steam grace mulak ulu districts grave and to know the relationship of service quality to improve customer satisfaction In Grace Pressure Cleaning Business Mulak Ulu Lahat. To be able to explain and portray objectively the formulation of the problem above, the writer uses the method of data collection in the form of Library Studies, Field Study consists of: Interview, observation and questionnaire. Data analysis technique used was qualitative and quantitative analysis techniques. Based on analysis of the correlation coefficient (r) value of 0.54, which means a positive correlation between service quality and customer satisfaction, value indicates the variable X (quality of service) with a variable Y (customer satisfaction) with proportional (unidirectional relationship) the greater the variable X then grew larger the value of the variable Y. To test the hypothesis that has been formulated rejected or accepted analytical tool used t-test and the results obtained: the value of t-table (0,025: 28) is 2.048 and the t-test of 2.82. Because t is greater than t table (3.37>1.701) then the hypothesis Ho is rejected and the value of the working hypothesis H1 is accepted. It can be concluded that there is influence between the variables X (quality of service) with a variable Y (customer satisfaction). Service quality has a positive correlation to customer satisfaction at the mercy of steam washing business mulak ulu Lahat regency, where the magnitude of the correlation is indicated by the number of correlation coefficient r of 0.54 (54%) Keywords : Service Quality, Customer Satisfaction